ASAL USUL FLUIDA MANIFESTASI PANAS BUMI DAN ESTIMASI TEMPERATUR RESERVOIR DENGAN PENDEKATAN ANALISIS ISOTOP PADA DAERAH DANAU RANAU, OGAN KOMERING ULU (OKU) SELATAN, SUMATERA SELATAN: ORIGIN OF GEOTHERMAL MANIFESTATION FLUID AND DETERMINATION OF RESERVOIR TEMPERATURE USING ISOTOPE ANALYSIS APPROACH IN THE LAKE RANAU AREA, SOUTH OGAN KOMERING ULU (OKU), SOUTH SUMATERA - Ibrahim, Mochamad Malik; Harnani, Harnani; Jati, Stevanus Nalendra; Abiyyu, Rayhan Khairunnan (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
The geothermal potential of the Lake Ranau area comes from the remains of magmatic activity from Mount Seminung. The geothermal manifestation in this area is in the form of hot springs which are thought to arise through geological structures. The existence of geothermal fluid manifestations is very interesting to research, especially regarding the origin and estimation of reservoir temperature using the δ18O and δ2H isotope composition approach. It is important to know the origin of fluid manifestations to determine the potential of geothermal systems from surface manifestations fluid related to magmatic, evaporation or rock interactions. This research method uses isotope analysis to determine the origin of geothermal fluid manifestations and isotope geothermometer to estimate reservoir temperature. Isotope sampling in geothermal manifestation fluids in Kota Batu Village was 3 samples and Lombok Village was 3 samples. The results of isotope analysis on the relationship graph between δ18O and δ2H show that all isotope samples in geothermal manifestation fluids come from meteoric water. The local meteoric water line value equation has a difference in the deuterium excess (DE) value compared to the global meteoric water line value equation. This change in DE value is due to the interaction and mixing process between geothermal fluid and rock (connate water) with the source of evaporation and precipitation from Lake Ranau. The results of isotope geothermometer calculations based on the isotope fractionation factor, it is estimated that the reservoir temperature is around ± 270 0C. Reservoir temperature estimates show that all isotope samples in geothermal manifestation fluids are classified as high temperatures.